Integrating grazing intensity regulation and livestock mobility restoration: A practical test for China’s next-generation rangeland policies - Jianguo Xue; Zunlan Luo; Zhang Chen; Ping Ge; Junchen Lv; Jianhui Huang; Ang Li (Agriculture, Ecosystems & Environment, 2026)

Synergistic surface engineering enables high-efficiency and stable operation of low-bromine wide-bandgap perovskite solar cells - Zhenzhen Peng; Zhimin Fang; Yi Zhang; Rongyao Lv; Yu-Ang Liu; Dehan Li; Bairu Li; Luozheng Zhang; Shuang Chen; Shangfeng Yang; Jianning Ding (Chemical Engineering Journal, 2026)

The synergistic effects of Algal and Bryophyte colonization on soil formation and microbial community assembly in acidic mine tailings - Xinyue Wang; Ang Lv; Yaojia Fu; Zhengyan Wang; Xiangjun Zhou; Lanzhou Chen (Environmental Research, 2026)

The Effects of Intraoperative Hypotension on Postoperative Acute Kidney Injury and Myocardial Injury: A Systematic Review and modelling study - Jiaxin Zhao; Xuan Li; Yunfei Lv; Rui Zhang; Ang Li; Gang Dong (Phenomics, 2026)

A lightweight vision based method for pre storage potato sorting in an automatic grading system - Danyang Lv; Mengdi Cheng; Ang Zhao; Ranbing Yang; Yongfei Pan; Shiting Lv; Jian Zhang; Tao Wang (Journal of Stored Products Research, 2026)

Recent research advances in the biological function and molecular mechanism of methylmalonic acid - Zi’ang Wang; Wenhui Cheng; Teng Wang; Yidi Zhang; Xin’e Shi; Yuqi Lv; Jianjun Jin (Journal of Zhejiang University-SCIENCE B, 2026)

Corrigendum to “The adaptability, distribution, ecological function and restoration application of biological soil crusts on metal tailings: A critical review” [Sci. Total Environ. 927 (2024), 172169] - Kejun Liao; Chaoqi Chen; Yan Li; Sijia She; Panpan Wang; Yue Tao; Ang Lv; Xinyue Wang; Lanzhou Chen (Science of The Total Environment, 2026)

Cold-summer and summer-snowfall trends and their impacts on vegetation in a warming Mongolian Plateau - Zhang Chen; Junchen Lv; Hao Jiang; Dongyang Lei; Jianguo Xue; Ang Li; Jianhui Huang (Journal of Arid Environments, 2026)

Impacts of synoptic weather patterns on Hefei's ozone in warm season and analysis of transport pathways during extreme pollution events - Feng Hu; Pinhua Xie; Jin Xu; Ang Li; Yinsheng Lv; Zhidong Zhang; Jiangyi Zheng; Xin Tian (Journal of Environmental Sciences, 2025)

Association between per- and polyfluoroalkyl substances with serum hepatobiliary system function biomarkers in patients with acute coronary syndrome - Fang Xiao; Ming Yang; Junli Lv; Jing Li; Mingmei Guo; WenJing Duan; Haoran Li; Ziwen An; Zhengyi Su; Ang Li; Yi Liu; Jingchao Lu; et al. (Journal of Environmental Sciences, 2025)

Ketamine Alters Specific Gene Expression Profiles by Transcriptome-Wide Responses in a Ketamine-Induced Schizophrenia-Like Mouse Model - Zhe Du; Xiu-mei Zhu; Peng Lv; Ying Pan; Xi-kai Hou; Ang Li; Dong Zhao; Jia-xin Xing; Jun Yao (Molecular Neurobiology, 2025)

Sufficient burial depth is a prerequisite for Chinese cyclina (Cyclina sinensis) to maintain normal life activities - Yurou Ma; Shiyu Yan; Zhengyu Shao; Guolong Zhou; Ang Hu; Yawei Bu; Huimin Wang; Xinqi Lv; Jianyu Liu; Yihua Chen; Zhiguo Dong (Aquaculture, 2025)

Progressing towards eco-friendly agricultural management: Utilizing Ginkgo biloba leaf litter for potato common scab control - Shoudong Wang; Ji-Ang Nie; Jiguang Wang; Minghao Lv; Qingquan Li; Mingcong Li; Bo Zhou; Zheng Gao; Wenchong Shi (Journal of Environmental Management, 2025)

Spatial-temporal distribution and emission of urban scale air pollutants in Hefei based on Mobile-DOAS - Zhidong Zhang; Pinhua Xie; Ang Li; Min Qin; Jin Xu; Zhaokun Hu; Xin Tian; Feng Hu; Yinsheng Lv; Jiangyi Zheng; Youtao Li (Journal of Environmental Sciences, 2025)

Dynamic interactions between Fe, Mn, S and C cycles in the Okinawa Trough seep sediments - Cuiling Xu; Qing Li; Taiheng Lv; Zhilei Sun; Ang Li; Ye Chen; Xilin Zhang; Feng Cai; Nengyou Wu (Global and Planetary Change, 2025)

Investigations of spatial-temporal distribution and regional transport in typical section of NO2 in eastern China using Mobile-DOAS - Zhidong Zhang; Pinhua Xie; Ang Li; Jin Xu; Xin Tian; Feng Hu; Zhaokun Hu; Yinsheng Lv; Youtao Li; Qiang Zhang; Wenqing Liu (Science of The Total Environment, 2025)

Role of per- and polyfluoroalkyl substances in the cardiorenal system: Unraveling crosstalk from the network of pollutants and phenotypes - Ming Yang; Jiaxin Zhao; Ziwen An; Haoran Li; Chaoying Ma; Junli Lv; Fang Xiao; Zhenzhen Tan; Longfei Li; Xiaoguang Zhang; Xuehui Liu; Yi Liu; et al. (Journal of Environmental Sciences, 2025)

Tissue accumulation and hepatotoxicity of 8:2 chlorinated polyfluoroalkyl ether sulfonate: A multi-omics analysis deciphering hepatic amino acid metabolic dysregulation in mice - Zhenzhen Tan; Ziwen An; Junli Lv; Fang Xiao; Longfei Li; Jing Li; Wenjing Duan; Mingmei Guo; Xiuli Zeng; Yi Liu; Ang Li; Huicai Guo (Journal of Hazardous Materials, 2025)

Breaking separation bottleneck in sucralose production: Clarifying the obscure mechanism and pre-embedding second solvents for highly selective separation of chlorinated product - Xiaoping Chen; Jiayan Lei; Zhoulin Lv; Zi'ang Chen; Shitong Lin; Zhenming Guo; Huadong Luo; Yingshu Wang; Jingjing Chen; Haohong Li; Huidong Zheng (Chemical Engineering Journal, 2025)

The adaptability, distribution, ecological function and restoration application of biological soil crusts on metal tailings: A critical review - Kejun Liao; Chaoqi Chen; Wenyan Ye; Jing Zhu; Yan Li; Sijia She; Panpan Wang; Yue Tao; Ang Lv; Xinyue Wang; Lanzhou Chen (Science of The Total Environment, 2024)

Low-temperature hydrogen production from waste polyethylene by nonthermal plasma (NTP)-assisted catalytic pyrolysis using NiCeOx/β catalyst - Jiaxing Song; Jiabao lv; Yuhan Pan; Jingyu Wang; Jun Wang; Ang Cao; Angjian Wu; Paul T. Williams; Qunxing Huang (Chemical Engineering Journal, 2024)

A neural m6A pathway regulates behavioral aggregation in migratory locusts - Xianliang Huang; Qing Li; Yanan Xu; Ang Li; Shanzheng Wang; Yusheng Chen; Chunrui Zhang; Xia Zhang; Hailin Wang; Cong Lv; Baofa Sun; Shaoqin Li; et al. (Science China Life Sciences, 2024)

Angiotoxic effects of chlorinated polyfluorinated ether sulfonate, a novel perfluorooctane sulfonate substitute, in vivo and in vitro - Zhenzhen Tan; Junli Lv; Haoran Li; Ziwen An; Longfei Li; Yijia Ke; Yi Liu; Xuehui Liu; Lei Wang; Ang Li; Huicai Guo (Journal of Hazardous Materials, 2024)

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

Integrated analysis of the transport process and source attribution of an extreme ozone pollution event in Hefei at different vertical heights: A case of study - Feng Hu; Pinhua Xie; Xin Tian; Jin Xu; Ang Li; Aurelia Lupaşcu; Tim Butler; Zhaokun Hu; YinSheng Lv; ZhiDong Zhang; Jiangyi Zheng (Science of The Total Environment, 2024)

Investigation of filtration performance and phosphorus removal in an electric field controlled dynamic membrane bioreactor - Long Chen; Miao Lv; Yang-Cheng Ding; Zi-Ang Lv; Dan-Na Ding; Di Wu; Haiping Yuan; Nanwen Zhu; Hua-Jun Feng (Chemical Engineering Journal, 2023)

MiR-1275 Targeting SPARC Promotes Gambogic Acid-Induced Inhibition of Gastric Cancer - Ang Cai; Pengfei Xia; Xiaokang Zhou; Yao He; Jun Lv (Biochemical Genetics, 2023)

McPrA - A new gas profile inversion algorithm for MAX-DOAS and apply to 50 m vertical resolution - Jiangyi Zheng; Pinhua Xie; Xin Tian; Jin Xu; Ang Li; Bo Ren; Feng Hu; Zhaokun Hu; Yinsheng Lv; Zhidong Zhang; Wenqing Liu (Science of The Total Environment, 2023)

Particulate organic emissions from incense-burning smoke: Chemical compositions and emission characteristics - Kai Song; Rongzhi Tang; Ang Li; Zichao Wan; Yuan Zhang; Yuanzheng Gong; Daqi Lv; Sihua Lu; Yu Tan; Shuyuan Yan; Shichao Yan; Jingshun Zhang; et al. (Science of The Total Environment, 2023)

A new insight into the CaO-induced inhibition pathways on PCDD/F formation: Metal passivation, dechlorination and hydroxide substitution - Xiaoxiao Wang; Jiabao Lv; Yuxuan Ying; Yunfeng Ma; Angjian Wu; Xiaoqing Lin; Ang Cao; Xiaodong Li; Jianhua Yan (Science of The Total Environment, 2023)

In situ reductive dehalogenation of groundwater driven by innovative organic carbon source materials: Insights into the organohalide-respiratory electron transport chain - Yang Yu; Yueyan Zhang; Yuqing Liu; Mengran Lv; Zeyi Wang; Li-lian Wen; Ang Li (Journal of Hazardous Materials, 2023)

Piezoelectric energy harvesting and dissipating behaviors of polymer-based piezoelectric composites for nanogenerators and dampers - Wenzheng Chen; Qitan Zheng; Yi Ang Lv; Yujie Chen; Qunfu Fan; Xunhuang Zhou; Hua Li; Qili Yu; Hezhou Liu (Chemical Engineering Journal, 2023)

Re-Exploring the Inflammation-Related Core Genes and Modules in Cerebral Ischemia - Wenjing Lv; Junqi Jiang; Yi Xu; Zhiyuan Chen; Zixuan Wang; Ang Xing; Xueping Zheng; Tingting Qu; Qi Wan (Molecular Neurobiology, 2023)

Antifungal Effects of Fusion Puroindoline B on the Surface and Intracellular Environment of Aspergillus flavus - Ping-Ping Tian; Yang-Yong Lv; Ang Lv; Wen-Jing Yuan; Shuai-Bing Zhang; Na Li; Yuan-Sen Hu (Probiotics and Antimicrobial Proteins, 2021)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.